POLA KOMUNIKASI ORGANISASI PEGAWAI SEKRETARIAT DPRD KABUPATEN PONOROGO PADA BAGIAN PERSIDANGAN DAN RISALAH - Budiarto, Agung (JI@P, 2021)
This study aims to analyze the influence of organizational culture motivation on employee performance in Ponorogo Regency's Regional People's Representative Assembly (DPRD,hereafter)Secretariat with leadership as a moderating variable. This research involved 44 state civil servants. The results of this studyshows that work motivation has a positive and significant effect on employee performance at Ponorogo Regency DPRD Secretariat. Increasing work motivation will further improve employee performance. In addition, organizational culture also has a positive and significant influence on employee performance at the Ponorogo Regency DPRD Secretariat where the better the organizational culture, the more employee performance will be. Leadership also has a positive and significant impact on employee performance at Ponorogo Regency DPRD Secretariat. The better the leadership role, the better employee performance will be. Leadership is also significantly able to strengthen the positive influence of work motivation on employee performance at Ponorogo Regency DPRD Secretariat. In other words, the role of leadership is able to moderate the influence of work motivation on employee performance and leadership can significantly strengthen the positive influence of organizational culture on employee performance at Ponorogo Regency DPRD Secretariat. Researchers found the fact that the role of leadership is able to moderate the influence of organizational culture on employee performance.